Youtube Channel Lapak Ganjar As A Communication Media For SME Product Promotioncontent Edition “Melki & Peppy Banting Setir? Jualan Marshmellow Viral Di Alun Alun Kidul? Lapak Ganjar Yogyakarta” - Nina Kusumawati; Lukman Lukman; Muhammad Ichsan; Sultan Himawan (Jurnal Scientia, 2023)
The advent of the internet and the rapid development of online media have recently resulted in digital media dominating society. The current digital revolution shows that the television model or television culture has changed from generation to generation due to changes in consumer behaviour. One of the most popular digital media today is YouTube. YouTube is a video-sharing platform founded in 2005. It is one of the most popular websites worldwide, with millions of daily active users. YouTube also has a partner program that allows users to earn money through advertisements on their videos. This allows content creators and businesses to monetize their content and generate additional revenue. Ganjar Pranowo used this to market MSME products in Central Java and its surroundings by utilizing the Youtube channel Ganjar Stalls. One UMKM product that uses the Ganjar stall is the Marshmellow product, which is a UMKM from the Jogja region. Usually selling manually in the South Square, then with the Ganjar booth, it becomes a promotional medium for these MSME products. With this promotion, we can expand the target market. From the data taken, a product to achieve its marketing goals in the intended market area must have marketing tools in the form of 4P, namely Product, Price, Place and Promotion.